Trabajos arqueológicos en Oxkintok durante el verano de 1991. - Vidal Lorenzo, C.; Rivera Dorado, Miguel; López de la Rosa, Edmundo; Muñoz Cosme, G. (Revista Española de Antropología Americana, 1993)
Sin resumen